The Influence of Product Quality and Price Perception on Consumer Purchase Decisions at Gallery Kosmetik Store Palopo - Paisal, M.; A. Metta, Yoksan; Lilingan, Bernadet; Amir, Indra; Gelyo, Alvin Johon Julian; Bakhtiar, Bakhtiar; Uleng, Budiarti Putri (Universitas Syiah Kuala, 2025)
This research was conducted at the Gallery Kosmetik Store in Palopo. The objects of this study are product quality and price perception in relation to consumer purchase decisions at Gallery Kosmetik Store Palopo. The purpose of this study is to measure product quality and price perception, as well as to examine their influence on consumer purchasing decisions at Gallery Kosmetik Store Palopo. The population of this research consists of consumers who have previously purchased products from the store. The sample includes 40 respondents, selected using incidental sampling. The data used in this research are both primary and secondary, collected through questionnaires distributed to the 40 selected respondents. The data analysis method used includes multiple linear regression, F-test, and t-test. Based on the tests, the study concludes that product quality and price perception simultaneously have a significant influence on consumer purchase decisions at Gallery Kosmetik Store Palopo. However, product quality does not have a significant partial effect on purchase decisions. Price perception, on the other hand, has a significant influence on consumer purchasing decisions. The implication of this research is that even though product quality does not have a significant partial effect, the store should still maintain high product quality to remain competitive. This is important to